2003
DOI: 10.1021/ed080p606
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Prelaboratory Tutorials and Computer-Based Probes in General Chemistry

Abstract: A strong desire to upgrade the general chemistry laboratory program at Georgia Southern University (GSU) through greater use of more modern laboratory techniques led to an NSF-DUE grant (0088586) to purchase computers and interfaced analytical probes. Included in the project was a complete restructuring of many of the traditional laboratory experiments to utilize the new equipment and also the development of Web-based laboratory tutorials to better prepare students for the experiments and to ease the transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 5 publications
1
17
0
1
Order By: Relevance
“…This reflects previous research in which visual presentations of experimental setups have been found to reduce student anxiety associated with using new equipment in the laboratory. 13 The visual nature of the videos may be appreciated to varying degrees by individual students, depending on their learning styles. 22 The use of online materials to guide pre-laboratory learning appears to fit well with the preferred styles of learning identified by students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This reflects previous research in which visual presentations of experimental setups have been found to reduce student anxiety associated with using new equipment in the laboratory. 13 The visual nature of the videos may be appreciated to varying degrees by individual students, depending on their learning styles. 22 The use of online materials to guide pre-laboratory learning appears to fit well with the preferred styles of learning identified by students.…”
Section: Discussionmentioning
confidence: 99%
“…4,13,21 Visual representations allow students to develop a mental picture of what they will be doing in laboratory classes, which may increase student confidence. 13 Inclusion of visual materials also caters to students who identify as visual learners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many authors report that as an observation, student confidence improves (or anxiety reduces). (Box et al, 2017;Chaytor et al, 2017;Chittleborough et al, 2007;Keen-Rocha, 2008;Kirk & Layman, 1996;Koehler & Orvis, 2003;Kolodny & Bayly, 1983;Limniou et al, 2009;Merritt, Schneider, & Darlington, 1993;Nicholls, 1998). In the analysis by Seery et al on the use of pre-laboratory videos to prepare for laboratory techniques, it was found that students' confidence increased significantly from before (Seery et al, 2017), although it should be noted that this effect was also observed in the work of Towns (Hensiek et al, 2016;Towns, Harwood, Robertshaw, Fish, & O'Shea, 2015) which also described in-laboratory demonstrations by students, but did not involve preparatory activity.…”
Section: Affective Experiencesmentioning
confidence: 99%
“…Actualmente no es difícil encontrar cursos telemáticos de química (Liu, Walter y Brooks, 1998;Judd, 1998, Robinson, 2000, Reeves y Kimbrough, 2004 o referencias al uso de Internet o de otras TICs en la enseñanza de la química: Internet como fuente de información (Varjola, 2000;Murov, 2001), uso de foros de discusión (Paulisse y Polik, 1999;Díez, 2005), enseñanza de laboratorio través de Internet y laboratorios virtuales (Cartwright y Valentine, 2002;Baran, Currie y Kennepohl, 2004;Cancilla, 2004), uso de tutoriales en formato web (Jiménez y Llitjós, 2005a;Donovan y Nakhleh, 2001;Koehler y Orvis, 2003), correo electrónico cooperativo (Pence, 1999), hipertexto cooperativo (Jiménez y Llitjós, 2005a), aplicaciones hipermedia (Tissue, 1996;Tissue, 1997) o la realización de ejercicios o deberes a través de Internet (Penn, Nedeff y Gozdzik, 2000).…”
Section: Introductionunclassified